CASE REPORT DIAGNOSIS AND TREATMENT OF VERNAL KERATOCONJUNCTIVITIS - Fariz Auliadi Khalil; Risa Ayu Nilmarani; Syarifah Rohaya; Diana Novita (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2023)
Background: Vernal keratoconjunctivitis (VKC) is a bilateral ocular allergic disease mediated by hypersensitivity reactions. VKC events occur in boys in the first decade of life and continue until puberty. Early identification and effective treatment are essential because the condition is recurrent and potentially burdensome to the patient's quality of life. This case report examines the diagnosis, management, and therapy options for patients with VKC and highlights the significance of the clinician's involvement in cases with VKC.Case Presentation: We report a case, a boy, 8 years old, came to the eye clinic at Cut Meutia Hospital with pain in both eyes, red eyes, decreased vision, and increased eye discharge. This complaint has been experienced for the past few years, and most appeared when the patient played under the sun or when the patient's allergy came. Examination showed mild conjunctival inflammation, pseudoptosis, and papillae on the limbus.Conclusion: The patient was diagnosed with VKC and received several treatments, including artificial tear and dexamethasone.